Collusion in multiobject auctions: An experimental evidence - Jindrich Matousek; Lubomir Cingl (Charles University in Prague, Institute of Economic Studies (IES), 2015)
We experimentally examine the attributes of two complex multi-unit auction mechanisms in the presence of an opportunity to collude among bidding participants due to a provision of a simple communication channel. The results suggest that the combinatorial bidding format does not bring higher efficiency. Allowing for communication increases efficiency in both examined auction formats. Bidders are able to split the auctioned goods in a cheap-talk collusive agreement, which results in a better allocation compared to the auction formats without the communication channel. Combinatorial bidding on packages makes the decision-making problem of bidders hard to process and cause inefficiencies, especially for designs with the large number of auctioned goods.
Keywords: C91; D43; D44; L96; 330; Combinatorial Auction; Communication; Collusion; Experiment